THE PRACTICE OF MISUSING PERSONAL DATA (NIK) IN THE REGISTRATION OF POLITICAL PARTIES PARTICIPATING IN THE 2024 GENERAL ELECTION AT BAWASLU KUDUS REGENCY ACCORDING TO POSITIVE LAW AND ISLAMIC CRIMINAL LAW - Jundan Muhammad Abda'u (Electronic Journal of Education, Social Economics and Technology, 2025)
Personal data can be defined as all information related to a person's identity. In Indonesia, the National Identification Number (NIK) is part of personal data, which is unique and inherently attached to an individual. However, during the registration process for the 2024 General Election (Pemilu), the Election Supervisory Body (Bawaslu) of Kudus Regency discovered misuse of NIK personal data. This misuse involved using citizens’ NIKs to register them as members of political parties in order to meet the requirements for political party participation in the election, without the data owners' knowledge. This study aims to understand how the misuse of NIK personal data occurred in the registration of political parties participating in the 2024 election at Bawaslu Kudus Regency, and how this practice is viewed under positive law and Islamic criminal law. This research is a qualitative study in the form of empirical juridical analysis. The data is sourced from interviews and literature. Once collected, the data is analyzed and presented using a descriptive-analytical method. The study found that political parties obtained personal NIK data from activities that required participants to bring copies of their Identity Cards (KTP). These data were then misused by registering them as part of the membership requirements for political parties participating in the election. According to Law Number 27 of 2022 concerning Personal Data Protection, such actions are punishable by imprisonment and/or fines, which can be imposed on individuals or corporations. Under Islamic law, the misuse of personal data is subject to ta'zir punishment, which includes imprisonment and additional sanctions in the form of fines.